Antifreeze Proteins. Report II. Occurrence in Nature - Gulevsky, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2009)
Multiple data on distribution of antifreeze proteins in nature are summarised in the paper. The main principles of their classification are presented. A variant of antifreeze protein classification depending on taxonomic categories of organisms, which they were found in, is proposed.